La autoeducación del hombre en la filosofía de la integralidad - Darós, W. R. (Revista Española de Pedagogía, 2018)
This article analyses the philosophy of M. F. Sciacca. This author exposes a whole conceptions of being. lt has three essential forms: reality, ideality, and morality. The human being shares in these three way of being in every human act. Therefore a whole and human education means to get ready everyone to face to reality (in this material world), to ideality (looking for the truth about thinks, persons, events), to morality (recognizing the truth and living according it; developing the person with objectivity). After that authority, discipline, sciences, human relations, selfcontrol, culture, work are considered as means for helping a person to become educated. The weakness in the conception of being and the decline in looking for truth (as wide as «esse») are symbols of a philosophy closed in the material world that reduces the possibilities of the human being and the humanistic education.
Keywords: autoeducación; filosofía; integralidad; Revista Española de Pedagogía